Scenario Evaluator for Electrical Resistivity Survey Pre‐modeling Tool. Issue 6 (23rd May 2017) - Terry, Neil; Day‐Lewis, Frederick D.; Robinson, Judith L.; Slater, Lee D.; Halford, Keith; Binley, Andrew; Lane, John W.; Werkema, Dale
Abstract: Geophysical tools have much to offer users in environmental, water resource, and geotechnical fields; however, techniques such as electrical resistivity imaging (ERI) are often oversold and/or overinterpreted due to a lack of understanding of the limitations of the techniques, such as the appropriate depth intervals or resolution of the methods. The relationship between ERI data and resistivity is nonlinear; therefore, these limitations depend on site conditions and survey design and are best assessed through forward and inverse modeling exercises prior to field investigations. In this approach, proposed field surveys are first numerically simulated given the expected electrical properties of the site, and the resulting hypothetical data are then analyzed using inverse models. Performing ERI forward/inverse modeling, however, requires substantial expertise and can take many hours to implement. We present a new spreadsheet‐based tool, the Scenario Evaluator for Electrical Resistivity (SEER), which features a graphical user interface that allows users to manipulate a resistivity model and instantly view how that model would likely be interpreted by an ERI survey. The SEER tool is intended for use by those who wish to determine the value of including ERI to achieve project goals, and is designed to have broad utility in industry, teaching, and research. Abstract : Article impact statement : SEER is a simple spreadsheet tool for rapid visualization of the likely outcome of 2D electrical resistivity surveys.